Early survival factor deprivation in the olfactory epithelium enhances activity-driven survival - François, Adrien; Laziz, Iman; Rimbaud, Stéphanie; Grebert, Denise; Durieux, Didier; Pajot-Augy, Edith; Meunier, Nicolas (Frontiers in Cellular Neuroscience, 2013)
The neuronal olfactory epithelium undergoes permanent renewal because of environmental aggression. This renewal is partly regulated by factors modulating the level of neuronal apoptosis. Among them, we had previously characterized endothelin as neuroprotective. In this study, we explored the effect of cell survival factor deprivation in the olfactory epithelium by intranasal delivery of endothelin receptors antagonists to rat pups. This treatment induced an overall increase of apoptosis in the olfactory epithelium. The responses to odorants recorded by electroolfactogram were decreased in treated animal, a result consistent with a loss of olfactory sensory neurons (OSNs). However, the treated animal performed better in an olfactory orientation test based on maternal odor compared to non-treated littermates. This improved performance could be due to activity-dependent neuronal survival of OSNs in the context of increased apoptosis level. In order to demonstrate it, we odorized pups with octanal, a known ligand for the rI7 olfactory receptor (Olr226). We quantified the number of OSN expressing rI7 by RT-qPCR and whole mount in situ hybridization. While this number was reduced by the survival factor removal treatment, this reduction was abolished by the presence of its ligand. This improved survival was optimal for low concentration of odorant and was specific for rI7-expressing OSNs. Meanwhile, the number of rI7-expressing OSNs was not affected by the odorization in non-treated littermates; showing that the activity-dependant survival of OSNs did not affect the OSN population during the 10 days of odorization in control conditions. Overall, our study shows that when apoptosis is promoted in the olfactory mucosa, the activity-dependent neuronal plasticity allows faster tuning of the olfactory sensory neuron population towards detection of environmental odorants.